Kontribusi Bantuan Siswa Miskin terhadap Keberlangsungan dan Keberlanjutan Pendidikan Siswa - Philip Suprastowo (Jurnal Pendidikan dan Kebudayaan, 2014)
Students Aid Program is a strategic implementation of the education policy regarding the equity and expansion of access for quality of education for all citizens without exception. This study presents a result of research that aims to figure out the contribution/role of the Program in the sustainability of the school in relation to the Drop out Rate (APS), Class Repetition Rate (AMK), students’ discipline and learning achievement, as well as education sustainability. The research uses survey and descriptive method in 12 sample districts/cities. The sample consists of 144 public schools, consisting of 48 schools from each level (elementary, junior high, and high school). The respondents in this study are school principals, teachers, parents, and students. The result shows that the Students Aid Program: 1) contributes positively towards the decreasing number of Drop out Rates. The Dropout Rates average decreases each year from 1,11% in 2010 to 0,66% in 2011, and 0,46 % in 2012; 2) contributes positively to decrease the Rates of Class Repetition Rate from 0,78% to 0,65% and the latest to 0,64%; 3) improves students’ learning discipline and motivation both in school and at home; 4) improves the students grade to 0,39 point in subjects tested in national examination (Indonesian Language, Math, and English). However, it is found that the Program has not been systematically oriented towards the students’ educational sustainability. ABSTRAK Bantuan siswa miskin (BSM) merupakan salah satu strategi implementasi kebijakan pemerataan dan perluasan akses pendidikan yang bermutu bagi semua warga negara tanpa kecuali. Kajian ini bertujuan untuk mengetahui kontribusi BSM terhadap keberlangsungan sekolah yang terkait dengan Angka Putus Sekolah (APS), Angka Mengulang Kelas (AMK), disiplin dan prestasi belajar serta keberlanjutan pendidikan. Penelitian dilakukan dengan survei dan descriptive research di 12 kabupaten/kota sampel. Satuan pendidikan yang diteliti sebanyak 144 sekolah negeri, masing-masing 48 SD, SMP, dan SMA, serta melibatkan responden kepala sekolah, guru, orangtua masing-masing 144 responden dan 576 siswa. Hasil penelitian menemukan bahwa BSM: 1) berkontribusi positif terhadap rendahnya APS, bahkan menurunkan dari rata-rata 1,11% pada tahun 2010 menjadi 0,66% di tahun 2011, dan pada tahun 2012 turun lebih rendah lagi menjadi 0,46%; 2) menekan rendahnya AMK, dari 0,78% menjadi 0,65%, dan 0,64% (berturut-turut pada tahun 2010, 2011 dan 2012); 3) meningkatkan disiplin dan motivasi belajar, baik di sekolah maupun di rumah; 4) berkontribusi meningkatkan nilai hasil belajar sampai 0,39 poin pada mata pelajaran Bahasa Indonesia, Matematika, dan Bahasa Inggris (diujikan secara nasional-UN/USBN); namun, diketahui bahwa BSM belum diorientasikan secara sistematis untuk keberlanjutan pendidikan siswa.